Inverse analysis of strain distributions sensed by distributed fiber optic sensors subject to strain transfer - Mahjoubi, Soroush; Tan, Xiao; Bao, Yi (Mechanical systems and signal processing, 2022)
•Strain distributions sensed by distributed fiber optic sensors are subject to strain transfer effect.•An inverse analysis is presented to convert measured strains into real strain distributions.•The method is applicable when the type and location of loading and strain field are unknown.•Multiple metaheuristic optimization algorithms are used and compared for the inverse analysis.•The method has been implemented to a prestressed concrete beam under four-point bending test. Strains measured by distributed fiber optic sensors with protective coatings can be different from the real strains in host matrix due to strain transfer effect. This study presents a novel inverse method to determine the real strain distributions in host matrix using strain distributions measured from distributed fiber optic sensors. Two different scenarios of strain distributions in host matrix are investigated, which have known and unknown types of strain fields, respectively. Three representative metaheuristic algorithms are respectively utilized in the inverse analysis, which are colliding bodies optimization algorithm, particle swarm optimization algorithm, and genetic algorithm. The performance of the proposed method was evaluated by analytical case studies and experimental testing of a prestressed concrete beam subjected to four-point bending. The results demonstrated high accuracy and efficiency of the proposed method. This study is expected to greatly advance distributed fiber optic sensing capabilities in measuring strain distributions for structural health monitoring.